Airway Responsiveness: Role of Inflammation, Epithelium Damage and Smooth Muscle Tension - K. I. Gourgoulianis; A. Domali; P. A. Molyvdas (Mediators of Inflammation)
The purpose of this study was the effect of epithelium damage on mechanical responses of airway smooth muscles under different resting tension. We performed acetylcholine (ACh) (10-5M)-induced contraction on tracheal strips from 30 rabbits in five groups (0.5, 1, 1.5, 2 and 2.5 g) before and after epithelium removal. At low resting tension (0.5-1.5g), the epithelium removal decreased the ACh-induced contractions. At 2g resting tension, the epithelium removal increased the ACh-induced contractions of airways with intact epithelium about 20%. At 2.5 g resting tension, the elevation of contraction is about 25% (p<0.01). Consequently, after epithelium loss, the resting tension determines the airway smooth muscles responsiveness. In asthma, mediators such as ACh act on already contracted inflammatory airways, which results in additional increase of contraction. In contrast, low resting tension, a condition that simulates normal tidal breathing, protects from bronchoconstriction even when the epithelium is damaged.